2017
DOI: 10.3201/eid2305.161905
|View full text |Cite
|
Sign up to set email alerts
|

Reassortant Clade 2.3.4.4 Avian Influenza A(H5N6) Virus in a Wild Mandarin Duck, South Korea, 2016

Abstract: A reassortant clade 2.3.4.4 avian influenza A(H5N6) virus was isolated from a fecal sample of a Mandarin duck (Aix galericulata) in South Korea during October 2016. This virus was genetically similar to H5N6 subtype virus isolates from China, Vietnam, Laos, and Hong Kong, including human isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 12 publications
(15 reference statements)
0
34
0
Order By: Relevance
“…Recently, other clade 2.3.4.4 viruses, such as H5N8 Group B and H5N6 Group C viruses, have also been reported from poultry and wild birds in various countries with Europe, Asia and Africa (Kwon et al., ; Lee, Bertran, Kwon, & Swayne, ; Pohlmann et al., ). This wide geographic distribution of clade 2.3.4.4 viruses and their infection of wild aquatic birds are of great concern.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, other clade 2.3.4.4 viruses, such as H5N8 Group B and H5N6 Group C viruses, have also been reported from poultry and wild birds in various countries with Europe, Asia and Africa (Kwon et al., ; Lee, Bertran, Kwon, & Swayne, ; Pohlmann et al., ). This wide geographic distribution of clade 2.3.4.4 viruses and their infection of wild aquatic birds are of great concern.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2003, a total of 7 Gs/GD‐like HPAIV outbreaks have reported in South Korea. Previous studies suggested that wild waterfowl played a major role in the spread of these HPAIV between China, South Korea and Japan (Kanehira et al, ; Kim et al, ; Kim et al, ; Kwon et al, ; Kwon et al, ; Lee et al, ; Mase et al, ; Sakoda et al, ; Uchida et al, ; Wee et al, ). Consistent with these findings, our phylogenetic analysis suggests that the outbreak in South Korea was initiated through multiple independent introductions with wild waterfowl origin clade 2.3.4.4A H5N8 HPAIV.…”
Section: Discussionmentioning
confidence: 99%
“…Complete genome analysis of the H5N6 HPAIVs isolated from poultry and wild birds in Japan between 2016 and 2017 demonstrated that 12 strains of the H5N6 HPAIVs isolated from poultry during this time could be classified according to their gene constellations into four groups (C1, C2, C4 and C6) by following the criteria established by Kwon et al. (Kwon et al., ). In addition, a single isolate from a mute swan in Kyoto, Japan belonged to another genotype (C5) (Takemae et al., ).…”
Section: Introductionmentioning
confidence: 99%